A method to modify the lineal energy-based quality factor for semiconductor microdosiemeters. (August 2018) - Payervand, Firouz; Raisali, Gholamreza; Moslehi, Amir
Abstract: A lineal energy-based quality factor, Q ( y ), has been provided for a spherical sensitive volume (SV) of 1 μm diameter. Significant errors may occur in determination of the dose equivalent by application of this quality factor to larger SVs as is common for semiconductor microdosiemeters. In this work a method is provided to correct Q ( y ) obtained with large SVs. The dose equivalent determined with spherical tissue SVs with different diameters up to 150 μm for mono-energetic protons and alpha particles with energies from 1 to 10 5  MeV per nucleon and 1–10 4  MeV per nucleon, respectively, is calculated with the corrected quality factor as well as the uncorrected quality factor by means of a Monte Carlo method. The results obtained reveal that by use of the corrected quality factor, the difference between the dose equivalents calculated for SVs with diameters larger than 1 μm reduces from a factor of 3 to less than 30% for the worst case.